Aru Shah and the nectar of immortality - Chokshi, Roshani (2022)
The Pandavas call on old friends, make new allies, and face fearsome trials as they embark on a mission to stop the Sleeper from accessing the nectar of immortality, but ultimately Aru must decide who deserves immortality--the devas or the asuras--and an unexpected answer comes from an unexpected place.
"Rick Riordan presents."
Ages 8-12.
Grades 4-6.
Keywords: Supernatural -- Fiction; Hindu mythology -- Fiction; Immortality -- Fiction; Novels